The Artist-Peasant Hug and the Valuation of Agricultural Products: The Case of the National Vintage Party, Argentina [el Abrazo Artista-Campesino y la Valoración de Los Productos Agrícolas: El Caso de la Fiesta Nacional de la Vendimia, Argentina] - Lacoste, P (Universidad de Tarapaca, 2021)
This paper studies the potential of the artist in the process of visibility and valuation of the peasant and agricultural products. It is detected that both actors (artist and peasant) have common problems due to the invisibility caused by the advance of mass culture and the rise of big brands with their advertising campaigns. These problems can be overcome through a strategic alliance between them to hold parties and shows around agricultural products. The subject is studied through an emblematic case: the National Harvest Festival, held in Argentina since 1936, which has enabled the value of Mendoza’s farmers and wines. The evolution of this show is studied, from the perspective of cultural artists and makers, and its way of contributing to the visibility and valuation of the territorial identity, its actors and products. © 2021, Universidad de Tarapaca. All rights reserved.